Russian and Turkic Worlds in Eurasia - N. E. Demeshko; G. L. Muradov; A. A. Irkhin; O. A. Moskalenko (Vestnik MGIMO-Universiteta)
This article delves into the dynamics of ethno-confessional factors influencing Russian-Turkish relations, exploring the Russian and Turkic worlds as geopolitical constructs within the Eurasian sphere. Employing a synthesis of critical and classical geopolitics methodologies, the study emphasizes the civilizational aspect as a pivotal element in the intricate interplay of competition and cooperation between Russia and Turkey in the Eurasian context. The research methodology integrates a civilizational perspective with critical geopolitics. The authors examine various strategies utilized by Turkey and Russia to implement ethnoconfessional policies in their quest for geopolitical influence. These strategies encompass the creation of narratives around 'fraternal nations', the promotion of shared historical, cultural, religious, linguistic, and heroic narratives; the cultivation of pro-Russian and pro-Turkish national elites; and the exploitation of ethno-national factors during domestic political crises. This analysis traces these phenomena from historical imperial contexts to contemporary interstate relations.Furthermore, the article underscores the significant impact of individual leadership in shaping the concept of the Turkic world, with a particular focus on the current President of the Turkish Republic, R.T. Erdogan. Erdogan is portrayed as a key figure actively advocating for and reinforcing the unity and identity of the Turkic world.